Tujuan Kemanfaatan Hukum Penerapan Restorative Justice dalam Penyelesaian Perkara di Kepolisian - Septianto, Herman; Kurniaty, Yulia; Hakim, Hary Abdul; Basri, B (Prosiding University Research Colloquium, 2023)
Restorative Justice is a new breakthrough in the settlement of cases outside the court, to restore it to its original state. Settlement of cases outside the court is an alternative choice to reduce Over Capacity in prisons and solutions to problems of time, costs, and dispute resolution procedures in court. The Republic of Indonesia Police apply the principles of Restorative Justice in settling criminal and civil cases through the Chief of Police Regulation (PERKAP) Number 8 of 2021. The purpose of this research is to analyze related to the application of Restorative Justice in terms of the legal benefits carried out by the Magelang City Police. The method used in this research is by using normative-empirical juridical. By using a statutory approach (Statute Approach) and a case approach (Case Approach). The data used in this research are laws, PERKAP 2021, books, articles, and other legal materials relevant to this research. The results of this study indicate that in the Magelang Police there were 11 (eleven) cases that were resolved using Restorative Justice. The settlement process with Restorative Justice provides legal benefits for the parties because the case is resolved by consensus so there is no grudge; the implementation procedure is quick and easy because it goes through two or three mediations; the parties do not bear the costs of the case; the type of punishment is non-prison in nature, for example in the form of compensation or social work.